Peran Budaya Miliran Yogyakarta dalam Mewujudkan Sustainable Development Goals (SDG) 11 Melalui Pendekatan Community Security - Harits Dwi Wiratma; Diansari Sholihah Amini; Raden Bambang Srigati; Tanti Nurgiyanti; Nur Annisa (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to analyze the role of Kampung Budaya Miliran, Yogyakarta, in realizing Sustainable Development Goal (SDG) 11, specifically target 11.3 on participatory and sustainable urbanization and target 11.4 on the protection of cultural heritage, using a community security approach. This perspective serves as an alternative in contemporary international relations, emphasizing the relevance of non-state actors and local communities at the grassroots level in responding to the global sustainable development agenda. The research employs a descriptive qualitative method with observation and interview techniques. The findings show that various community-based cultural activities—such as cultural carnivals, art studios, Javanese script education (pawiyatan aksara Jawa), traditional ceremony training (pranata cara), and communal traditions—function not only as practices of cultural preservation but also as mechanisms for strengthening social cohesion and protecting local identity. The community security approach contributes to the implementation of community-based initiatives by Miliran residents in developing and expressing their programs amid the current era of modernization. Kampung Budaya Miliran stands as one example of a village in Yogyakarta that is able to apply global values in line with SDG 11 targets 11.3 and 11.4. Therefore, the contributions of local communities and residents can be considered an alternative and innovative approach within international relations studies. This perspective strengthens the analysis of community security cases in relation to sustainable development, particularly SDG 11 targets 11.3 and 11.4.